Programmed gRNA Removal System for CRISPR-Cas9-Mediated Multi-Round Genome Editing in Bacillus subtilis - Lim, Hayeon; Choi, Soo-Keun (Frontiers in Microbiology, 2019)
CRISPR/Cas9 has become a simple and powerful genome editing tool for many organisms. However, multi-round genome editing should replace single-guide RNA (sgRNA) every round, which is laborious and time-consuming. Here, we have developed a multi-round genome editing system in which genome editing and the programmed removal of the sgRNA have sequentially occurred in a growth-dependent manner in Bacillus subtilis. The system contains two plasmids, one containing a cas9 gene and the other containing two sgRNAs and a donor DNA for homology directed repair. The two sgRNAs are chromosome-targeting (sgRNAct) and self-targeting (sgRNAst) under the control of a constitutive promoter and sporulation-specific promoter, respectively. In the growth phase, the sgRNAct is transcribed and complexed with the Cas9 to edit the chromosomal target, while the sgRNAst is transcribed in the sporulation phase and complexed with the Cas9 to attack its own plasmid. Therefore, the system automatically makes the cell ready for next-round genome editing during cultivation. The system was approved through the sequential deletion of eight extracellular protease genes in the B. subtilis, suggesting that it can be used for versatile applications in multi-round genome editing.